An Application of Distribution-Neutral Fiscal Policy - Gupta, Sanjeev (IMF Working Papers; Working Paper ;, 2018)
Distribution neutral fiscal policy refers to a structure of taxes and transfers that keep the income distribution unchanged even after positive or negative shocks to an economy. This is referred to as a Strong Pareto Superior (SPS) allocation which improves the standard Pareto criterion by keeping the degree of inequality, but not the absolute level of income intact. We apply this methodology to India to compute SPS tax rates and determine their proximity to actual tax rates. Limited available data on income and expenditure shows that the official policies so far are close to desired benchmark level. Our methodological contribution will be enriched further with more detailed income tax and transfer data.